Making sense of multi-level and multi-actor governance of recovery in Ukraine - Oksana Udovyk; Ievgen Kylymnyk; Daniel Cuesta-Delgado; Guillermo Palau Salvador (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
This paper sheds light on the complex recovery governance in Ukraine by providing a snapshot of the evolving national recovery actors' networks and examining them within a multi-level governance framework, using interviews, social network analysis, and a sense-making workshop. It highlights the ambiguity of the multi-level recovery governance structure in Ukraine, which shows characteristics of decentralization while representing a rather centralized machine and tends to be multi-actor while leaving some groups of actors behind. The paper offers suggestions for improvement but concludes that a bottom-up recovery process that leverages the decentralization potential and multi-actor energy is needed to benefit the current system constellations. In general, the paper provides a starting point for further research and analysis to deepen our understanding of Ukraine's emerging recovery governance landscape.
Keywords: D85; H77; O20; R58; 330; decentralization; social network analysis; bottom-up; recovery governance